2018
DOI: 10.1177/1528083718775980
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into tensile strength of noncrimp three-dimensional orthogonal woven structure

Abstract: Noncrimp three-dimensional orthogonal carbon weave is a specific type of three-dimensional woven fabric which is expected to have high performance as composite reinforcement. In this paper, two different orthogonal weaves in terms of carbon fiber tow type and binder yarns insertion density are produced, and a comprehensive study on the tensile strength of carbon composite reinforcements is conducted. The fiber volume fraction and mechanical performance are found to be affected by these two weave parameters. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Noobing samples were produced on a self-designed machine based on a uniaxial process. 26 In general, there are four different types of yarn in Noobing textile namely: warp yarn (y yarn), weft yarn (x yarn), binder yarn (z yarn), and holder yarn. The holder yarn locks the x and z yarns in the textile structure at each end of each picking motion in the fabric production.…”
Section: Methodsmentioning
confidence: 99%
“…Noobing samples were produced on a self-designed machine based on a uniaxial process. 26 In general, there are four different types of yarn in Noobing textile namely: warp yarn (y yarn), weft yarn (x yarn), binder yarn (z yarn), and holder yarn. The holder yarn locks the x and z yarns in the textile structure at each end of each picking motion in the fabric production.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of finite element modeling required the geometry of the unit cell to be created. A meso-geometrical model of the 3D fabric was used according to Minapoor et al [35]. The unit cells of the two fabric preforms are shown in Figure 5.
Figure 5.A unit cell of the non-crimp 3D orthogonal structure: (a) low yarn density, and (b) high yarn density.
…”
Section: Methodsmentioning
confidence: 99%
“…14 The results showed that increase in temperature imposed a slight impact on the composites’ on-axis tensile features. The impact properties of this structure are other considerable properties that were studied by Hu et al 15 Minapoor et al, in another work, 10 investigated the tensile strength of a novel NC3DOW with two different yarn densities. This fabric was produced by a self-designed loom.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, designing a composite with a high fiber volume fraction in this fabric is easier than others. 10,11 Some studies have been conducted to investigate the mechanical behavior of NC3DOW fabric. Karahan et al 12 investigated the internal geometry of NC3DOW composite by image processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation